Linear growth in prepubertal children with atopic dermatitis. Issue 2 (1st August 1998) - Patel, L; Clayton, P E; Addison, G M; Price, D A; David, T J
Abstract : OBJECTIVE: To define the evolution of prepubertal growth in atopic dermatitis and the factors influencing that growth pattern. METHODS: Height and height velocity over two years, weight, triceps and subscapular skin fold thickness, and bone age were assessed in 80 prepubertal patients with atopic dermatitis and a control group of 71 healthy prepubertal school children. RESULTS: Height standard deviation scores (SDS) and height velocity SDS did not differ between patients and controls, and were not influenced by body surface area affected by atopic dermatitis, topical glucocorticoid potency, or coexisting asthma. However, height SDS ( r  = −0.37) and height velocity SDS ( r  = −0.31) correlated inversely to age in patients but not in controls. A greater proportion (z = 2.84) of patients than controls had year 2 height velocity SDS less than −1.96. Patients had a mean delay in bone age of 0.22 years and 0.41 years at the beginning of year 1 and year 2 of the study, respectively. The delay in bone age correlated positively with age ( r  = 0.39) and duration of atopic dermatitis ( r  = 0.39), and negatively with height SDS ( r  = −0.51) and height velocity SDS ( r  = −0.38). CONCLUSIONS: Prepubertal children with atopic dermatitis are not short compared with controls. However, as they approach the teenage years their height velocity decreases, the proportion of children with extremely low height velocity increases, and the delay in bone age increases. These features are consistent with the pattern of growth seen in people with constitutional growth delay.